2007
DOI: 10.1080/10826080701202577
|View full text |Cite
|
Sign up to set email alerts
|

Communicating (Birth Defects) Prevention Information to a Hmong Population in Wisconsin: A Study of Cultural Relevance

Abstract: Compelling research from the early 1990s indicated a strong correlation between the consumption of the B-vitamin folic acid and the prevention of a serious birth defect (neural tube defect) in infants. This article examines numerous challenges the author faced when attempting to produce a culturally relevant folic acid brochure for Hmong women of childbearing age in LaCrosse, Wisconsin, part of a broad folic acid education program. An immediate challenge arose from the traditional Hmong belief that birth defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…12 This view of fatalism is similar to one of the 4 sources of illness understood in traditional Hmong culture-natural, personal, social, and supernatural. 22 Supernatural etiology posits that serious illness is attributed to spiritual causes; [23][24][25] illnesses such as cancer can be caused by the loss of a soul, the offending spirit of ancestors, or by encountering frightening spirits 16,26 These spiritually-based health beliefs can be a barrier to cancer screening because the individual will try to turn to spiritual remedies instead of seeking preventive Western care, such as a Pap test. For exam-ple, they might seek out a shaman to conduct a spiritual healing ceremony to retrieve the lost soul by fulfilling the needs of an ancestor or household spirit 22,27,28 As a result of such alternative strategies, the individual might delay the cancer-screening process and refuse biomedical preventive care, fearing that such actions might offend the spirit further.…”
Section: Discussionmentioning
confidence: 99%
“…12 This view of fatalism is similar to one of the 4 sources of illness understood in traditional Hmong culture-natural, personal, social, and supernatural. 22 Supernatural etiology posits that serious illness is attributed to spiritual causes; [23][24][25] illnesses such as cancer can be caused by the loss of a soul, the offending spirit of ancestors, or by encountering frightening spirits 16,26 These spiritually-based health beliefs can be a barrier to cancer screening because the individual will try to turn to spiritual remedies instead of seeking preventive Western care, such as a Pap test. For exam-ple, they might seek out a shaman to conduct a spiritual healing ceremony to retrieve the lost soul by fulfilling the needs of an ancestor or household spirit 22,27,28 As a result of such alternative strategies, the individual might delay the cancer-screening process and refuse biomedical preventive care, fearing that such actions might offend the spirit further.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has identified a wide array about causal beliefs related to birth defects, including using drugs and alcohol (Cohen et al 1998;Griffiths and Kuppermann 2008), smoking (Bello et al 2013), maternal impression (Castro 1995;Callister and Vega 1998;Cohen et al 1998;Snow 1983), eating certain foods (Cheng 1990;Dryden 1990), heredity (Cohen et al 1998;Dryden 1990;Griffiths and Kuppermann 2008;Nelson et al 2009;Ojofeitimi and Elegbe 1984), God's will (Ojofeitimi and Elegbe 1984), lunar or solar eclipses (Callister and Vega 1998;Snow 1983), intake of medications or vaccines (Griffiths and Kuppermann 2008;Mazzotta et al 1999;Sanz et al 2001), parental punishment or karma (Cheng 1990;Ojofeitimi and Elegbe 1984;Snow 1983;Viste 2007), advanced maternal age (Bello et al 2013) and receiving x-rays during pregnancy (Bentur et al 1991). However, these studies are largely ethnographic, focusing on unique, traditional cultures or very specific ethnic populations, often emphasizing folk beliefs and supernatural attributions.…”
Section: Introductionmentioning
confidence: 99%